2013
DOI: 10.1289/ehp.1205727
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Arsenic Exposure and Blood Glutathione and Glutathione Disulfide Concentrations in Bangladeshi Adults

Abstract: Background: In vitro and rodent studies have shown that arsenic (As) exposure can deplete glutathione (GSH) and induce oxidative stress. GSH is the primary intracellular antioxidant; it donates an electron to reactive oxygen species, thus producing glutathione disulfide (GSSG). Cysteine (Cys) and cystine (CySS) are the predominant thiol/disulfide redox couple found in human plasma. Arsenic, GSH, and Cys are linked in several ways: a) GSH is synthesized via the transsulfuration pathway, and Cys is the rate-limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 52 publications
3
62
0
2
Order By: Relevance
“…In another cross-sectional study, a total of 378 participants from areas with different arsenic water concentrations were recruited and their blood GSH and GSSG were evaluated through HPLC. The results showed that the interquartile range increase in water arsenic was negatively associated with blood GSH and urine arsenic levels [21]. These observations are consistent with other observations in animal studies where arsenic exposure influences GSH levels in blood [22,23].…”
Section: Erythrocytessupporting
confidence: 91%
“…In another cross-sectional study, a total of 378 participants from areas with different arsenic water concentrations were recruited and their blood GSH and GSSG were evaluated through HPLC. The results showed that the interquartile range increase in water arsenic was negatively associated with blood GSH and urine arsenic levels [21]. These observations are consistent with other observations in animal studies where arsenic exposure influences GSH levels in blood [22,23].…”
Section: Erythrocytessupporting
confidence: 91%
“…19 Males had higher blood GSH concentrations, less oxidized blood GSH E h values, and higher blood SAM levels than females (p < 0.0001). Eversmokers also had higher GSH concentrations, less oxidized blood GSH E h values, and higher SAM levels than never-smokers.…”
Section: Blood Glutathione Redox Status and Global Methylation Of Permentioning
confidence: 88%
“…Participants were selected based on well water As (wAs) exposure such that the final study sample represented the full range of wAs concentrations in the region, as described previously. 19 Participants were excluded if they were pregnant and/or planned to become pregnant within 3 mo, were currently taking nutritional supplements (within the past 3 mo) or had known diabetes, cardiovascular or renal disease or other diseases known to be associated with oxidative stress.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Downstream metabolite, cysteine is regarded as a rate-limiting substrate in glutathione (GSH) biosynthesis [32]. Notably, GSH is known as a principle antioxidant required for liver detoxification reactions.…”
Section: Biological Interpretation Of the Metabolic Variationsmentioning
confidence: 99%